Eddy current modelling using multi-layer perceptron neural networks for detecting surface cracks - Salaheddine Harzallah; R. Rebhi; M. Chabaat; A. Rabehi (Fracture and Structural Integrity)
A new method for computing fracture mechanics parameters using computational Eddy Current Modelling by Multi-layer Perceptron Neural Networks for detecting surface cracks. The method is based upon an inverse problem using an Artiﬁcial Neural Network (ANN) that simulates mapping between Eddy current signals and crack proﬁles. Simultaneous use of ANN by MLP can be very helpful for the localization and the shape classification of defects. On the other side, it can be described as the task of reconstructing the cracks and damage in the plate profile of  an  inspected  specimen  in  order  to  estimate  its  material properties. This is accomplished by inverting eddy current probe impedance measurements that are recorded as a function of probe position, excitation frequency or both. In eddy current nondestructive evaluation, this is widely recognized as a complex theoretical problem whose solution is likely to have a significant impact on the detection of cracks in materials